Review paperInsights into Behçet’s disease - Shahneh, Fatemeh Zare; Babalo, Zohreh; Baradaran, Behzad; Sepehr, Koushan Sineh (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Behçet’s disease is a chronic relapsing multi-organ inflammatory disorder characterized as a triad of oral and genital ulcers, uveitis. Characteristic manifestations of Behçet’s disease are joints, skin, central nervous system and gastrointestinal tract involvement. Behçet’s disease has a complicated genetic etiology. However, epidemiological studies recommend that genetic factors have a significant role in its pathogenesis, the same as other autoinflammatory disorders. Antigenic stimuli, antigen-presenting cells, T cells, monocyte, neutrophil and endothelial cells are most important parts of the pathology of the disease. Inflammatory response was triggered by an infectious agent in a genetically susceptible host. Understanding the pathogenesis based on the molecular mechanism of the disease highlights the new therapeutic modalities. Enhanced inflammatory activity and over-expression of proinflammatory cytokines are the striking features of Behçet’s disease, and they are accordant with the result in other auto inflammatory disorders. Moreover, there is evidence of antigen-driven immune response in Behçet’s disease, but it probably advances in further innate immune reactivity. New therapeutic modalities target specific and nonspecific suppression of the immune system. The diagnosis is a clinical one, and although there is no single laboratory test enough for the diagnosis of Behçet’s disease. In this paper, a new aspect of the studies on genetic susceptibility, immunopathogenesis of Behçet’s disease and novel treatment modalities will be discussed.